HEPATOTOXICITY AND NEPHROTOXICITY ACTIVITY OF ETHANOL EXTRACT OF ABIES WEBBIANA LINDL.LEAVES - D.K. YADAV,; A.K. GHOSH,; B. KUMAR, (International Journal of Pharma and Bio Sciences, 2016)
The present study was conducted to evaluate the effect of alcoholic extract A.webbiana leaves Lindl on liver and kidney. Wistar rats were divided into three groups (n=3) for hepatotoxicity and nephrotoxicity. Alcoholic leaves extract of A.webbiana was evaluated for protective effects against CCl4 induced hepatotoxicity and cisplatin induced nephrotoxicity. Hepatotoxicity studied by comparing parameters to control group, CCl4 treated group and induced CCl4 followed by alcoholic extract group such as SGOT, SGPT, SALP, bilurubin and also compare histopathological examination of liver tissue. Nephrotoxicity studied by comparing parameters to control group, cisplatin treated group and induced cisplatin followed by alcoholic extract group serum BUN, serum creatinine, serum protein and % change in body weight and histological examination of kidney tissues. Effect of ethanol extract of Abies webbiana at dose of 400 mg/kg was studied by comparing the liver and kidney parameters with carbon tetra chloride and cisplatin induced as control respectively. Ethanol extracts of Abies webbiana at dose 400 mg/kg was found to be hepato and nephro protective effect and histopathological examination also support these activity. It is concluded that alcoholic extract possess hepatoprotective and nephroprotective activity significantly.